In-field assessment of EPSPS amplification on fitness cost in mixed glyphosate-resistant and glyphosate-sensitive populations of Palmer amaranth (Amaranthus palmeri). Issue 6 (24th November 2022) - Cahoon, Charles W.; Jordan, David L.; Tranel, Patrick J.; York, Alan C.; Riggins, Chance; Seagroves, Richard; Inman, Matthew; Everman, Wesley; Leon, Ramon
Abstract: Comparing fitness of herbicide-resistant and herbicide-susceptible weed biotypes is important for managing herbicide resistance. Previous research suggests there is little to no fitness penalty from amplification of the 5-enolpyruvylshikimate-3-phosphate synthase ( EPSPS ) gene (a mechanism of glyphosate resistance) in Palmer amaranth ( Amaranthus palmeri S. Watson) in controlled studies in the greenhouse or growth chamber. A field study was conducted in North Carolina at three locations naturally infested with A. palmeri to determine vegetative, reproductive, and germination fitness of plants with and without EPSPS amplification grown season-long with cotton ( Gossypium hirsutum L.). Seed number was not correlated with EPSPS copy number. However, when plants were binned into two groups, those having an EPSPS copy number ≥2 (relative to reference genes) and those having an EPSPS copy number <2, plant fresh weight and seed number were 1.4 and 1.6 times greater, respectively, for plants with fewer than 2 EPSPS copies. Amaranthus palmeri height and seed germination, and yield of cotton, did not differ when comparing the two binned groups. These data suggest that A. palmeri plants with EPSPS amplification are relatively less fit in the absence of glyphosate, but this reduced fitness does not translate into differences in interference with cotton.